Sistem Peminjaman Buku Perpustakaan dengan Identifikasi Kode Quick Response (QR) - Kurniawan Firman Syah; Sukirman Sukirman (Jurnal Pendidikan Informatika (EDUMATIC), 2023)
Currently at SMK Muhammadiyah 01 Boyolali the process of managing library book lending services is still manual with library ledgers and there is no computerized system, so this results in fewer effective services and is prone to transaction data errors. This study aims to create a library book lending system with quick response (QR) code identification to overcome problems in the current library service process. The system development method uses Waterfall which consists of analysis, design, implementation, and testing. The analysis phase of collecting data on library services through observation and interviews. The system process design stage is described using use case and activity diagram. System functionality testing uses black box testing and usability testing uses a QUIS questionnaire which consists of several parameters, namely: overall reaction to the software, screen, terminology and system information, and system capabilities. Our findings are in the form of an information system that can assist the library service process. In addition, the results of the black box testing of all components in this system run as expected and the validity and reliability tests obtain valid and reliable results for each parameter. Thus, it can be concluded that this system can be used in optimizing library services.